Pengaruh Penerapan Good Corporate Governance dan Kompetensi Dewan Direksi Terhadap Kinerja Keuangan Perusahaan pada Masa Pandemi Covid-19: (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Dadan Kurniawan; Agrianti Komalasari; Fitra Dharma; Niken Kusumawardani (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to examine the effect of the implementation of good corporate governance and the competence of the board of directors in banking companies listed on the Indonesia Stock Exchange in 2019-2023. This study is a type of quantitative research using secondary data from the Indonesia Stock Exchange and the official website of each company. The sampling method used purposive sampling and obtained a sample of 12 companies with an observation period of 5 years so that the number of research samples was 57 data. The data analysis technique used was multiple linear regression using SPSS 27 software. Based on the results of the study, it was found that managerial ownership had an effect on financial performance. However, this study did not find any influence between the board it-related background variables and institutional ownership on financial performance.